The impact of long-term azithromycin on antibiotic resistance in HIV-associated chronic lung disease. Issue 1 (7th February 2021) - Abotsi, Regina E.; Nicol, Mark P.; McHugh, Grace; Simms, Victoria; Rehman, Andrea M.; Barthus, Charmaine; Ngwira, Lucky G.; Kwambana-Adams, Brenda; Heyderman, Robert S.; Odland, Jon Ø.; Ferrand, Rashida A.; Dube, Felix S.
Selection for resistance to azithromycin (AZM) and other antibiotics such as tetracyclines and lincosamides remains a concern with long-term AZM use for treatment of chronic lung diseases (CLD). We investigated the impact of 48 weeks of AZM on the carriage and antibiotic resistance of common respiratory bacteria among children with HIV-associated CLD. Nasopharyngeal (NP) swabs and sputa were collected at baseline, 48 and 72 weeks from participants with HIV-associated CLD randomised to receive weekly AZM or placebo for 48 weeks and followed post-intervention until 72 weeks. The primary outcomes were prevalence and antibiotic resistance of Streptococcus pneumoniae (SP), Staphylococcus aureus (SA), Haemophilus influenzae (HI) and Moraxella catarrhalis (MC) at these timepoints. Mixed-effects logistic regression and Fisher's exact test were used to compare carriage and resistance, respectively. Of 347 (174 AZM, 173 placebo) participants (median age 15 years (IQR 13–18), female 49%), NP carriage was significantly lower in the AZM (n=159) compared to placebo (n=153) arm for SP (18% versus 41%, p <0.001), HI (7% versus 16%, p=0.01) and MC (4% versus 11%, p=0.02); SP resistance to AZM (62% (18 out of 29) versus 13% (8 out of 63), p <0.0001) or tetracycline (60% (18 out of 29) versus 21% (13 out of 63), p <0.0001) was higher in the AZM arm. Carriage of SA resistant to AZM (91% (31 out of 34) versus 3% (1 out of 31), p <0.0001), tetracycline (35% (12 out of 34) versus 13% (4 out of 31), p=0.05) and clindamycin (79% (27 out of 34) versus 3% (1 out of 31), p <0.0001) was also significantly higher in the AZM arm and persisted at 72 weeks. Similar findings were observed for sputa. The persistence of antibiotic resistance and its clinical relevance for future infectious episodes requiring treatment needs further investigation. 48 weeks of azithromycin reduced carriage of S. pneumoniae, H. influenzae and M. catarrhalis but promoted antibiotic resistance in S. pneumoniae and S. aureus ; antibiotic-resistant S. aureus persisted at 72 weeks from randomisation https://bit.ly/3L0m5tU